Overall Survival and Complication Rates in the Treatment of Liver Carcinoma: A Comparative Study of Ultrasound, Computed Tomography, and Combined Ultrasound and Computed Tomography Guidance for Radiofrequency Ablation - Chia-Hsien Chien; Chia-Ling Chiang; Huei-Lung Liang; Jer-Shyung Huang; Chia-Jung Tsai (Diagnostics, 2025)
Background: Liver cancer is a major health concern worldwide. Radiofrequency ablation is a safe treatment option that can be guided by either ultrasound, computer tomography (CT), or fluoroscopy. Although ultrasound-guided radiofrequency ablation is commonly used in clinical practice, radiofrequency ablation guided by CT is more precise but requires more time and does not offer real-time monitoring, which may result in complications such as pneumothorax or organ damage. Objectives: In this study, we investigated the effect of ultrasound, CT, and combined ultrasound/CT guidance on patient survival and complication development. Methods: A total of 982 radiofrequency ablation sessions conducted on 553 patients were analyzed. Clinical outcomes were assessed during follow-up to determine the survival and recurrence rates of malignant tumors. Results: Overall, the three guidance approaches exhibited significant differences in terms of tumor size, number, complication development, and treatment duration. However, no significant differences were observed in survival rate. A comparison of the effect of CT guidance and ultrasound guidance on complication development revealed a higher odds ratio for CT guidance in some cases. A comparison of combined ultrasound/CT guidance and ultrasound guidance revealed nonsignificant differences in complication development. A comparison of CT guidance and combined ultrasound/CT guidance revealed a higher odds ratio for CT guidance in some cases. Radiofrequency ablation is a safe and effective treatment for liver tumors. However, CT has an increased incidence of complications. Conclusions: Combined ultrasound/computer tomography guidance is recommended for patients with multiple or large tumors or tumors near the hepatic dome or diaphragm.